Room temperature of liquified petroleum gas (LPG) sensor based on p-La2O3/n-Fe2O3 - Wan Johari, Wan Hanapi (2008)
Recently, owing to environment and safety aspect, interest in utilization of gas sensor is increasing. Gas sensor is used to detect hazardous gas in order to avoid it from spread to the environment. Lanthanum oxide and iron (III) oxide was chosen because of their availability and cost effective. Performance of using lanthanum oxide and iron (III) oxide as sensing element were investigated. Detection of liquefied petroleum gas in this research reported has a very long response time due to the chemical properties of lanthanum oxide. The p-La2O3/n-Fe2O3 sensor has detected the LPG 20 minutes after start flowing the gas inside the modified plastic bottle. This paper also describe the study on thermal stability of each substrate has been done using Thermogravimetric Analysis (TGA). Thermogravimetric Analysis is a type of testing that is performed on samples to determine changes in weight in relation to change in temperature. Such analysis relies on a high degree of precision in three measurements: weight, temperature, and temperature change. Lanthanum oxide shows that at 8000C their original form will be transform into another phase of oxide such as LaO and LaO2. Iron (III) oxide still remains their original form to the end of the sintered.